Efficient Management of High-Throughput Screening Libraries with SAVANAH. (February 2017) - List, Markus; Elnegaard, Marlene Pedersen; Schmidt, Steffen; Christiansen, Helle; Tan, Qihua; Mollenhauer, Jan; Baumbach, Jan
High-throughput screening (HTS) has become an indispensable tool for the pharmaceutical industry and for biomedical research. A high degree of automation allows for experiments in the range of a few hundred up to several hundred thousand to be performed in close succession. The basis for such screens are molecular libraries, that is, microtiter plates with solubilized reagents such as siRNAs, shRNAs, miRNA inhibitors or mimics, and sgRNAs, or small compounds, that is, drugs. These reagents are typically condensed to provide enough material for covering several screens. Library plates thus need to be serially diluted before they can be used as assay plates. This process, however, leads to an explosion in the number of plates and samples to be tracked. Here, we present SAVANAH, the first tool to effectively manage molecular screening libraries across dilution series. It conveniently links (connects) sample information from the library to experimental results from the assay plates. All results can be exported to the R statistical environment or piped into HiTSeekR (http://hitseekr.compbio.sdu.dk ) for comprehensive follow-up analyses. In summary, SAVANAH supports the HTS community in managing and analyzing HTS experiments with an emphasis on serially diluted molecular libraries.